CLINICAL CHARATERISTICS OF GINGIVAL ENLARGMENT (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the clinical characteristics of gingival enlargement in a group of Vietnamese people. Methods: The study was conducted on 47 patients diagnosed with gingival enlargement. The clinical charscteristics included: localized nature, gingival enlargement location, gingival enlargement position according to anterior and posterior correlation, degree of gingival enlargement, rate of teeth having gingival enlargement and level of bone resorption.  Results: Gingival enlargement was observed mainly at anterior teeth (78.8%), located mainly at papillae (70.2%).
Keywords: Gingival enlargement.